Anti-inflammatory effect of acute stress on experimental colitis is mediated by cholecystokinin-B receptors - YEGEN, BERRAK; ÖZBEYLİ, DİLEK; GÜLPINAR, MEHMET ALİ (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
We aimed to investigate the effects of electric shock (ES) on the course of experimental colitis and the involvement of possible central and peripheral mechanisms. In Sprague-Dawley rats (n = 190) colitis was induced by intracolonic administration 2,4,6-trinitrobenzenesulfonic acid (TNBS). The effects of ES (0.3-0.5 mA) or the central administration of corticotropin-releasing factor (CRF; astressin, 10 mug/kg) or cholecystokinin (CCKB; 20 mug/kg) receptor antagonists and peripheral glucocorticoid receptor (RU-486; 10 mg/kg) or ganglion (hexamethonium; 15 mg/kg) blockers on TNBS-induced colitis were studied by the assessment of macroscopic score, histological analysis and tissue myeloperoxidase activity. ES reduced all colonic damage scores (p < 0.05-0.01), while central CRF (p < 0.05-0.001) and CCKB receptor (p < 0.05-0.01) blockers or peripheral hexamethonium (p < 0.05-0.01) and RU-486 (p < 0,05) reversed stress-induced improvement. ES demonstrated an anti-inflammatory effect on colitis, which appears to be mediated by central CRF and CCK receptors with, the participation of hypothalamo-pituitary-adrenal axis and the sympathetic nervous system. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: cholecystokinin (CCK); colitis; hypothalamo-pituitary-adrenal (HPA) axis; stress; sympathetic nervous system (SNS); CORTICOTROPIN-RELEASING-FACTOR; GASTROINTESTINAL-TRACT; ARGININE-VASOPRESSIN; GENE-EXPRESSION; SOCIAL STRESS; C-FOS; CRF; RATS; INFLAMMATION; ACTIVATION